Fatherlessness in first-century Mediterranean culture: The historical Jesus seen from the perspective of cross-cuitural anthropology and cultural psychology - Aarde, Andries van (Hervormde teologiese studies, 1999)
In the peasant sociey of Jesus' world the family revolved around the father. The father and the mother were the source of the family, not only in the biological sense, but because their interaction with their child rencreated the structures of society. In first-century Mediterranean culture, fatherlessness led to marginalization. Seen against the background of the patriarchal mind set of Israelites in the Second Temple period, a fatherless son would have been without social identiy. He would have been debarred from being called child of Abraham (that is child of God) and from the privilege of being given a daughter in marriage. He would be denied access to the court of the Israelites in the Temple. In this article, with the help of cross-cultural anthropology and cultural psychology, the life of the historical Jesus is explained in social-scientiic terms against the background of the mariage regulations determined by the Temple. The historical Jesus is seen as someone who sufered the stigma of being fatherless but who trusted God as father.